Contrived competition regulation and deregulation in America - Vietor, Richard H. (Belknap Press of Harvard Univ. Press, 1994)
This is the story of a revolution in American industry: the massive deregulation of markets by the government starting in the late 1970s. After an era of New Deal controls that lasted forty years, and in response to a stagnating economy, a new intellectual and political consensus developed in support of competitive markets. Beginning in 1978, Congress enacted a raft of deregulatory reforms, which federal agencies implemented during the early 1980s